2001
DOI: 10.1093/nar/29.1.312
|View full text |Cite
|
Sign up to set email alerts
|

rSNP_Guide, a database system for analysis of transcription factor binding to target sequences: application to SNPs and site-directed mutations

Abstract: rSNP_Guide is a novel curated database system for analysis of transcription factor (TF) binding to target sequences in regulatory gene regions altered by mutations. It accumulates experimental data on naturally occurring site variants in regulatory gene regions and site-directed mutations. This database system also contains the web tools for SNP analysis, i.e., active applet applying weight matrices to predict the regulatory site candidates altered by a mutation. The current version of the rSNP_Guide is supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 16 publications
0
18
0
1
Order By: Relevance
“…The promoter region has been implicated in regulation of transcription and mRNA stability [15]. Variants in this region of a gene may have functional significance by affecting transcription and resulting in reduced or abnormal protein expression [17][18][19]. Alternatively, the variant may tag a causative variant located outside of the H2AFX locus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The promoter region has been implicated in regulation of transcription and mRNA stability [15]. Variants in this region of a gene may have functional significance by affecting transcription and resulting in reduced or abnormal protein expression [17][18][19]. Alternatively, the variant may tag a causative variant located outside of the H2AFX locus.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the coding region of H2AFX is genetically conservative and that genetic variants outside the coding region, or geneenvironmental interaction, may play an important role in the development of malignancies. It is known that the promoter and 3 0 -UTR regions of a gene have functions in regulating transcription, messenger RNA (mRNA) stability, and gene production [15] and that single-nucleotide polymorphisms (SNPs) are the common genetic variants in these core and proximal promoter regions [16], and thus searching for functional variants in the promoter and 3 0 -UTR regions or regulatory regions of the gene [17][18][19] becomes important. Recently, two molecular epidemiology studies demonstrated that H2AFX promoter polymorphisms may alter susceptibility to cancers, including non-Hodgkin lymphoma [20] and breast cancer [21].…”
Section: Introductionmentioning
confidence: 99%
“…The results of these studies suggest that the coding region of H2AFX is genetically conservative and that genetic variants outside the coding region, environmental factors, or gene-environment interaction may play an important role in the development of malignancies. It is known that the promoter and 3′UTR regions of a gene have functions in regulating transcription, mRNA stability, and gene production [23] and that SNPs are the common forms of genetic variations in these core and proximal promoter regions [24], and thus searching for functional variants in the promoter, 3′UTR or regulatory regions of the gene [25][26][27] becomes important. Recently, Novik et al reported that the promoter SNP −417G > A (rs2509049) in H2AFX has a protective association with non-Hodgkin lymphoma [28].…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27] Para rSNP existe una base de datos especializada denominada rSNP_Guide, la cual contiene versiones curadas de rSNP validados de manera experimental, así como mutaciones en elementos reguladores generados también de forma experimental. 28 Una forma de identificar in silico rSNP requiere en principio el reconocimiento de un elemento de respuesta con alta probabilidad de ser funcionalmente relevante y la subsiguiente búsqueda de variaciones que puedan repercutir en la transcripción del gen en cuestión. La identificación de secuencias reguladoras cis por métodos informáticos ha progresado en grado considerable.…”
Section: Enfoques Bioinformáticos Para La Identificación De Rsnpunclassified